Improving Engine Performance and Low Temperature Properties of Blended Palm Biodiesel Using Additives. A Review - Obed M., Ali; R., Mamat (Trans Tech Publications Inc., 2013)
After the oil crisis in 1973, renewable sources of energy are gianing more interest due to multiplicity feedstocks and lower pollution compared with fossil fuels. Wide agricultural lands through the world are not fully benefited. Therefore, farming should include the production of non-food products which are suitable to weather conditions of these lands. This leads to the production of biodiesels as renewable fuel for the domestic energy market, to reduce the dependence on fossil fuels. Biodiesel have gained a large interest of researches during the last few decades, the major reason to find an alternative fuel, is the increasing worry about the greenhouse gas effects and environmental regulations. Blended palm biodiesel with ordinary diesel fuel have been approved as a fuel for compression ignition engines without any modification. Palm biodiesel application is relatively limited to its poor cold flow properties characteristics. Many experimental studies are conducted to evaluate the influence of using different additives with Palm Oil Methyl Ester (POME) biodiesel/diesel blends on fuel properties (viscosity, cold properties, anticorrosiveness, cetane number, heat content, volatility) and engine performance. This article provides a literature survey on the effect of different additives to improve the fuel properties of palm biodiesel and engine performance. The review shows that the additive usage in palm biodiesel is accompanying for improving the cold flow properties and better engine performance as well emission regulation.